Stories of mermaids - Punter, Russell; Guicciardini, Desideria (Usborne Publishing Ltd London, 2007)
Three original mermaid tales for children who are just beginning to learn how to read. Meet a scheming mermaid lurking to sabotage the Great Seahorse Race, a mermaid on a journey to the spooky Pirates' Graveyard and a mermaid who just loves to dance! Delicately illustrated by Desideria Guicciardini. Usborne Young Reading has been developed with reading experts from Roehampton University.